Students' Level of Understanding of Static Electricity at MAN 1 Merangin - Delvia Anjani; Fauzan Sulman; Aminah Zb; Boby Syafrinando; Salman Al Farisi (Lembaga Penelitian dan Pendidikan Mandala, 2026)
This study was conducted to evaluate students' level of understanding of static electricity in physics at MAN 1 Merangin, as well as to identify obstacles encountered during the teaching process. The methodological approach used was descriptive qualitative, with data collected through surveys. The research population involved some students from class XII IPA 2, while the research sample consisted of 11 students selected using purposive sampling. The instruments used included a questionnaire to measure concept mastery and another questionnaire to detect learning difficulties. These instruments were designed to assess basic concept understanding, learning obstacles, and aspects of the material that students found most difficult.The findings show that students' level of understanding of static electricity concepts is moderate. No students were classified as having the lowest level of understanding. Specifically, 3 students (27.27%) were in the partially understood category, while the other 8 students (72.73%) were classified as fully understanding. This indicates that most students have successfully mastered the concept of static electricity, from definitions and interactions between charges to the process of charge formation. However, students had difficulty internalizing the concept of electric flux and its application to various forms of symmetry. These findings reinforce the view that even though students have prior knowledge, abstract concepts such as electric field interactions and the principle of symmetry remain major challenges in physics learning.Overall, the findings of this study indicate the urgency of improving students' understanding of static electricity concepts by applying more efficient learning techniques, utilizing various representation methods, and strengthening the foundations of key concepts before exploring topics involving quantitative and conceptual aspects. This study is expected to serve as a guide for teachers in developing pedagogical approaches that are more in line with students' characteristics and learning patterns.